2020
DOI: 10.1155/2020/1358674
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Specificity Protein 1 Is Involved in Phloretin-Induced Suppression of Prostate Cancer

Abstract: Phloretin is a flavonoid existed in various plants and has been reported to possess anticarcinogenic activity. However, the anticancer mechanism of phloretin in prostate cancer (PCa) remains unclear. Here, our in vitro and in vivo experimental data demonstrate that phloretin inhibits the phosphorylation and the activation of EGFR and then inhibits its downstream PI3K/AKT and MEK/ERK1/2 pathways in PCa cells. Inhibition of these two pathways further decreases expression of Sp1 by inhibiting Sp1 gene transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Further studies will be necessary to fully elucidate the pathways regulated by phloretin and how it exerts its anti-inflammatory effects on IL-6. Phloretin-mediated inhibition of VEGF might involve the phosphatidylinositol 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) pathway, but this, too, will need further study to confirm [38,39]. Furthermore, in vitro studies, while an important first step in the study of molecular responses and pathways, can only provide a limited view into the complex mechanisms that underlie human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will be necessary to fully elucidate the pathways regulated by phloretin and how it exerts its anti-inflammatory effects on IL-6. Phloretin-mediated inhibition of VEGF might involve the phosphatidylinositol 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) pathway, but this, too, will need further study to confirm [38,39]. Furthermore, in vitro studies, while an important first step in the study of molecular responses and pathways, can only provide a limited view into the complex mechanisms that underlie human disease.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-tumoral effect of antioxidants in prostate cells with normal prostate-specific antigen (PSA) would be reversed into pro-tumoral effect in prostate cells with high PSA [ 75 , 76 , 77 ], which was the most common for PCa. Another mechanism of treatment effect of phloretin in PC3 cell line was that it could efficiently induce apoptosis [ 13 ]. In the concentration of 100 μM, they also found that anti-apoptotic proteins, such as Bcl-2, were decreased and pro-apoptotic proteins, such as Bax and caspase-3, were increased [ 13 ].…”
Section: Phloretin Bph and Pcamentioning
confidence: 99%
“…Another mechanism of treatment effect of phloretin in PC3 cell line was that it could efficiently induce apoptosis [ 13 ]. In the concentration of 100 μM, they also found that anti-apoptotic proteins, such as Bcl-2, were decreased and pro-apoptotic proteins, such as Bax and caspase-3, were increased [ 13 ].…”
Section: Phloretin Bph and Pcamentioning
confidence: 99%
See 1 more Smart Citation
“…Suppressing the former could interrupt the three-hit process and decrease APC in the prostate, whereas suppressing the latter could downregulate OS in the prostate. Moreover, the ability of phloretin to induce apoptosis, which can attenuate the development of prostate cancer, was also researched [ 11 ]. This makes phloretin a possible and attractive derivative to prevent BPH.…”
Section: Introductionmentioning
confidence: 99%